A propos de Cordylobia rodhaini Gedoelst et la description d’une nouvelle espèce affine afrotropicale (Diptera, Calliphoridae) - Lehrer, A.Z.; Goergen, Georg E. (2006)
One makes the re-description of the myiasigenes species CordylobiarodhainiGedoelst and the description of a new species found in Togo, Cordylobia ebadianan. sp. One represents the details of their male genitalia and one gives the keys of identification of the four known species of genus.